The idea of creativity, the creativity behind an idea - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Many people believe that creativity is important to their line of work – from salespeople to accountants, lawyers to administrators – but few people seem to believe that they have what it takes to be creative. Even fewer people think that their employers are helping them to be creative. What lies behind the mystical creativity holy grail that makes it so elusive yet incredibly seductive? Creativity expert Fredrik Härén provides some insights into how we think about creativity and what makes companies like Google, Apple and Pixar tick.